Existência e multiplicidade de soluções para diferentes classes de equações de Choquard - Böer, Eduardo de Souza (2023)
In the present work we deal with two classes of Choquard Elliptic Equations with unbounded and sign-changing potentials, considering Fractional and Kirchhoff operators and nonlinearities with exponential critical growth. Applying variational techniques and classical theorems, under suitable conditions, we prove existence and multiplicity of solutions.